Measuring the Level of Radiation in some Dry Food Imported in the Markets of AL-Kifil - City and Estimating Excess of Cancer Risk Factor in this Town (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The radioactive contamination is one of the main causes of cancers. Since the Dry food imported with the different global products is uncensored and is increasing, it is necessary to carry out periodic radiological surveys of all types in our local markets ,the aim of this project is to highlight of radiation level of same food with a statistical procedure for patients with cancer in the AL-Kifil region, there for the activity concentrations of 40K, 226Ra and 232Th radionuclide's calculated in 20 types of Dry food samples were taking from markets in (AL-Kifil City) by using γ-ray spectrometry with NaI(Tl) detector. The mean activity concentrations of 226Ra is (25.3+9.3) Bq/kg, 232Th(28.4+7.6)Bq/kg, and 40K (501.2+158.4) Bq/kg the activity concentration of 40K higher than the international recommended values (412) Bq/kg the reason is due to the nature of the terrain enjoyed by the industrialized countries for this type of food, which reflected negatively on the number of cancer patients in the digestive system of the population of the city of Kifil, the highest compared to other areas of the province of Babylon, an average of 33 cases.